Rapid screening for group B Streptococcus in near-term pregnant women by Granada™ biphasic broth. (3rd July 2017) - Wassef, Mona; Ghaith, Doaa; Abdella, Rana M. A.; Kamel, Mohamed
Abstract: Background : Prenatal screening for group B Streptococcus (GBS) colonization can reduce the incidence of neonatal GBS infections. We aimed to improve the screening-based approach of GBS in a limited resources antenatal care clinic by using Strep B Granada™ Biphasic Broth. Methods : This study included 80 pregnant women between 35 and 37 weeks of gestation, who attended the antenatal care clinic of Kasr El-Aini University Hospital from November 2013 to January 2014. Two high vaginal swabs were collected, then transported using Amies transport medium. One vaginal swab was processed by conventional culture-based methods on 5% sheep blood agar plates. The other swab was immersed in 3 mL selective enrichment broth (Granada™ Biphasic Broth bioMérieux). Results : Among 80 pregnant women, GBS was detected in 9 (11.25%) of the studied cases within 18–24 hours. Detection of orange-red colonies in GBS Granada broth was 100% specific for the presence of beta-hemolytic group B streptococci. Conclusion : Using Granada biphasic broth media was easy, affordable and shortened the turnaround time needed for the detection of GBS by conventional culture methods. Routine screening of pregnant women for vaginal GBS colonization by Granada™ Biphasic broth would allow properly timed prenatal antimicrobial prophylaxis to prevent possible neonatal infections.